2016
DOI: 10.1002/chem.201600497
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Spirocyclic Oxindoles through Regio‐ and Stereoselective [3+2] or [3+2]/[4+2] Cascade Reaction of α,β‐Unsaturated Imines with 3‐Isothiocyanato Oxindole

Abstract: On the basis of asymmetric regioselective [3+2] or [3+2]/[4+2] cascade reaction of 3-isothiocyanato oxindoles with C=C and C=N bonds of α,β-unsaturated methanesulfonamides, diversified S-containing heterocyclic spirooxindole derivatives could be obtained in high yields along with good to excellent diastereo- and enantioselectivities under mild conditions in the presence of cinchona alkaloid-derived organocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 111 publications
0
8
0
1
Order By: Relevance
“…In 2016, Min Shi et al reported regioselective and stereoselective [3+2] cascade reaction of ,-unsaturated imines 10 with 3-isothiocyanato oxindoles 11 to produce spirocyclic oxindole derivatives 12 and 13 (Scheme 3). 17…”
Section: Synthesis Of Oxindoles Skeletonmentioning
confidence: 99%
“…In 2016, Min Shi et al reported regioselective and stereoselective [3+2] cascade reaction of ,-unsaturated imines 10 with 3-isothiocyanato oxindoles 11 to produce spirocyclic oxindole derivatives 12 and 13 (Scheme 3). 17…”
Section: Synthesis Of Oxindoles Skeletonmentioning
confidence: 99%
“…In 2016, Shi's group studied the reactivity of different azadienes in the reaction with 3-Isothiocyanate oxindoles 42, catalysed by chiral bifunctional thioureas (Scheme 9) [30]. The α,βunsaturated imines 43, 45, and 47 were used as electrophiles to initiate the cascade sequence, followed by a thiolactam ring closure, which depended on the starting imine.…”
Section: Formal Cycloaddition Reactions With 3-isothiocyanate Oxindolesmentioning
confidence: 99%
“…These transformations can be conducted under mild organocatalytic conditions in a highly stereoselective manner. Thus, various mono-and bis-spiroheterocycles and their fused analogues have been constructed featuring thioimidazolidinone-spirooxindoles [26][27][28][29][30], fused-thioimidazolidinone-spirooxindoles [31], thiopyrrolidinone-spirooxindoles , fused-thiopyrrolidinone-spirooxindoles [53][54][55][56], thiooxazolidinone-spirooxindoles [57][58][59], and thio-1,2,4-triazolidinone [60].…”
Section: Introductionmentioning
confidence: 99%